(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Girish Karnad’s taking to myth and legend in his plays was more an act of impulse rather than intention. Perhaps it was inevitable for Karnad who was exposed to traditional forms of theatre in childhood. The three kinds of theatre between which he moved, swivelled and wrote plays, were the company Natak, Yakshagana and the western theatre, and he must have been influenced by them, whatever the reason, whether it is the influence of traditional theatre upon him or it is his incapacity to invent new stories as he confesses, he had rightly chosen to use myths and legend for his plays. He feels they are very much relevant today, and hence, seeks to adapt myths and folk forms in his plays. Thus he effects a synthesis between the ancient and the modem to serve his purpose of using the past to illuminate the present. Girish Karnad in his ‘Hayavadana’ used the same myths to project the theme of fundamental ambiguity of human life. He makes the play an interesting study of man’s quest for a complete and wholesome experience of life. For this, he combines the transposed heads plot of Mann with Hayavadana story which is entirely Karnad’s own invention. This is how Kamad makes use of a myth. He takes them only in parts and the rest he supplements with his imagination.